Peran Keterlibatan Pelanggan dalam Meningkatkan Minat Beli Ulang Pada SPBU Coco 41.573.01 Pertamina di Solo - Prasetya Mulya Diantara Putra; Sekar Pandanarum; Paulus Wardoyo; DC. Kuswardani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The research method used is Quantitative research with a questionnaire study approach. This research was conducted on customer experience, Affection With Service, customer involvement, Repurchase Interest, and customer satisfaction at Pertamina COCO 41.573.01 Gas Station in Solo. The population in this study was Pertamina COCO 41.573.01 Gas Station in Solo, the research sample return technique was based on the principle of non-probability sampling. Data processing in this study used smartPLS SEM (Partial Least Square - Structural Equation Modeling) Software. The results of this study are Affection With Service has an effect on repurchase intention, Customer satisfaction has an effect on customer involvement, Customer involvement has an effect on Affection With Service, Customer involvement has an effect on repurchase intention, Customer experience has an effect on Affection With Service, and Customer experience has no effect on customer involvement.